Towards Building Web Based Augmented Reality Application for Pre-School Children - Sule Tekkesinoglu; Mohd Shahrizal Sunar; Cik Suhaimi Yusof (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The goal of this work is to present a concept for web based Augmented Reality. We have many examples of Augmented Reality systems in different field from military applications to medical applications, from entertainment to manufacturing. In this paper we worked on how virtual environments can be combined with web based applications. Internet users need web sites for many reasons in daily life. On the other hand, Augmented Reality is one of the popular fields on virtual environment technologies that it would be useful to associate these two technologies. In this study JavaScript were used as main language to build Augmented Reality application supported by three different libraries each with a specific role. The libraries which are used through coding are Flartoolkit, Papervision3D, and Flex SDK. The outcome of this combined algorithms shows that the method is accomplished web based Augmented Reality for preschool children to provide educators a way to teach students with deeper, and more meaningful experiences in the academy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2659